Case Study of the Entrepreneurial Orientation Role in the Sustainability of Family Business in Central Java - Nathania Emmanuel Puteri Subagyo; Susilo Toto Rahardjo (Budapest International Research and Critics University, 2022)
This research explores the role of entrepreneurial orientation in maintaining the sustainability of family businesses in Central Java, Indonesia. Family businesses have a significant contribution to the Indonesian economy, so maintaining the sustainability of the family business is important. However, in increasingly competitive industrial conditions and a dynamic economic environment, vulnerable family businesses are unable to survive. Building from research related to the influence of entrepreneurial orientation in family business, this study provides an in-depth understanding of the role of entrepreneurial orientation in creating innovation and maintain the competitive position of a family business across generations, so that the sustainability of related family businesses can be maintained. This research was conducted by explorative case study methods with two generations and senior business employees at a family business in Central Java, Indonesia. Meanwhile, the results showed that family orientation plays a role in maintaining the sustainability of the family business through its contribution to improving performance and company expansion